Adaptation to land constraints: Is Africa different? - Headey, Derek D.; Jayne, Thomas S. (Elsevier, 2014)
Since the seminal works of Malthus and Boserup, scientists have long debated the impact of population growth and land constraints on the wellbeing of rural people. Today these concerns are particularly relevant to Africa, with its rapid population growth, very small farms, and chronic food insecurity. In this paper we examine adaptation to falling land-labor ratios using a comprehensive theoretical framework in which households faced with binding land constraints can respond in three ways: intensifying agricultural production, diversifying out of agriculture, and reducing fertility rates. Using cross-country data and drawing upon the existing literature, we reach three conclusions. First, population density is associated with reduced fallows and more intensive use of land but not fertilizer use or irrigation, indicating major challenges in achieving sustainable intensification or agricultural productivity growth. Second, there is little evidence of successful non-farm diversification in response to land pressures in Africa from domestic or international income sources. Third, rural Africans in land constrained countries desire smaller families, but have thus far benefited little from family planning policies. These findings underscore the need for a coordinated multi-sectoral approach to sustainably reduce poverty in the region.